EFEKTIVITAS MEDIA PEMBELAJARAN CANVA TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN IPAS DI SD N TUKANGAN - Panji Arya Kusuma; Fauzan Akhmad Alfian Muzakki; Abra Setyo Dirgantara; Keysha Mustika Dewiningrum; Danuri (STKIP Subang, 2024)
Learning achievement can be said to be the level of measuring a student's ability to accept the subject matter provided during the learning process. Learning achievement can be improved through several things, one of which is the use of learning media. The results of the learning achievement of class V students at SD N Tukangan tend to be low because the learning process is still conventional or teacher-centred and has not implemented technology in learning. This research aims to determine the effectiveness of the Canva learning media on student learning achievement in science and science subjects at SD N Tukangan. This research is experimental research with a Quasi-Experiment research method using One-Group Pretest-Posttest. Hypothesis testing was carried out using the one sample t-test with t_count = 11.589 and sig value. (2-tailed) is 0.000<0.05 then H0 is rejected and Ha is accepted. So it can be concluded that the Canva learning media is effective in improving student learning achievement in science and science subjects at SD N Tukangan.